COMPARATIVE STUDIES ON PHYTOCHEMICAL SCREENING OF FOUR DIFFERENT FLOWERS – COUROUPITA GUIANENSIS, BAUHINIA PURPUREA, STENOLOBIUM STANS, AND PLUMERIA RUBRA - SAI NANDHINI R,; NIRMALA NITHYA R, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study aims to investigate the phytochemical from the aqueous and methanol flower extracts of four significant medicinal plants, namely, Couroupita guianensis, Bauhinia purpurea, Stenolobium stans, and Plumeria rubra. Methods: The different flowers such as C. guianensis, B. purpurea, P. rubra, and S. stans were collected from Avadi and Koyambedu market, Chennai. Standard procedure was followed for the qualitative analysis of phytocompounds. Results: Preliminary phytochemical analysis resulted that the methanolic flower extract of four plants has rich bioactive compounds comparably to the aqueous flower extracts. Tannins, saponins, flavonoids, terpenoids, and steroids were highly present in B. purpurea compared the other three flowers. Only plant P. rubra contains the rich source of cardiac glycosides in methanolic flower extract. Conclusion: From the results of the current study, we conclude that the methanolic extract of B. purpurea flower has bulk phytocompounds and can be used as a traditional medicine to treat a variety of diseases.